Adjoint equations and analysis of complex systems - Marchuk, G. I. (Guriĭ Ivanovich), 1925- (Mathematics and its applications (Springer Science+Business Media), 1995)
This is the first monograph to present the fundamentals of adjoint equation theory and perturbation algorithms, exemplifying their applications by solutions of complex problems of mathematical physics. The earlier Russian version (1992) has been completely revised and supplemented with many new results for this edition, thus offering a unique compilation of the author's research in many areas of applied mathematics over the years. The first part of the book describes the theory of adjoint equations and perturbation algorithms and gives examples of applications to problems. Nonlinear problems and statements of inverse problems based on methods of adjoint equations and perturbation are considered. The second part focuses on the applications of adjoint equations theory and perturbation algorithms to the solution of concrete problems, such as global and regional environmental protection, interaction between atmosphere and ocean, and data assimilation problems. This volume will be of great value to a wide range of researchers, workers and engineers interested in creating new technologies for designing and planning experiments, while solving concrete problems, especially for those working on numerical mathematics.